High-efficiency luminescent solar concentrators for flexible waveguiding photovoltaics - Correia, Sandra F. H.
Here we present a new concept on lightweight and mechanically flexible high-performance waveguiding photovoltaics through the fabrication of cylindrical luminescent solar concentrators (LSCs) of commercial poly(methyl methacrylate)-based plastic optical fibers coated with an Eu3+-doped organic-inorganic hybrid layer. Our optimized fiber LSC displays an effective optical conversion efficiency of 20.7 +/- 1.3% and a power conversion efficiency of 2.5 +/- 0.2% in the absorbing spectral region of the active layer (300-380 nm), values that are among the larger ones reported so far for UV-absorbing devices. Moreover, the measured optical conversion efficiency was used to calculate the self-absorption and transport efficiencies of the LSCs yielding values close to the unit Conventional LSCs are usually made of rigid glass or plastics with limited flexibility, hampering its applicability. The approach proposed here might then open new opportunities for cost-effective sunlight collection and wearable solar-harvesting fabrics for mobile energy with negligible self-absorption and transport losses. (C) 2015 Elsevier B.V. All rights reserved.